1991
DOI: 10.1007/bf00037466
|View full text |Cite
|
Sign up to set email alerts
|

A variational approach to the magneto-elastic buckling problem of an arbitrary number of superconducting beams

Abstract: Based upon a variational principle and the associated theory derived in three preceding papers, an expression for the magneto-elastic buckling value for a system of an arbitrary number of parallel superconducting beams is given. The total current is supposed to be equal both in magnitude and direction for all beams, and the cross-sections are circular. The expression for the buckling value is formulated more explicitly in terms of the so-called buckling amplitudes, the latter following from an algebraic eigenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…By using Taylor series of the trigonometric differential operators in Eq. (8), it follows from the exact governing Eq. (60) that…”
Section: The Plate Subjected An Exponential Distributed Perturbation mentioning
confidence: 99%
See 1 more Smart Citation
“…By using Taylor series of the trigonometric differential operators in Eq. (8), it follows from the exact governing Eq. (60) that…”
Section: The Plate Subjected An Exponential Distributed Perturbation mentioning
confidence: 99%
“…The refined theory for plate bending problems of magnetoelasticity was discussed in our previous work [1]. It was shown that in the magnetoelastic plate problems the approximate governing equations of refined theory have the same form as those of other well-know theoretical models of magnetoelastic plates, such as the Pao-Yeh model [2] from the axiomatic system, the Eringen-Maugin model [3,4] from the rational mechanical theorem, the magnetic couple model [5] and the magnetic force model [6] from the magnetic dipole model, and the variational principle model [7,8]. This property is very helpful to show the validity of the new refined plate theory.…”
Section: Introductionmentioning
confidence: 99%
“…By using Eqs (30), (31) and Taylor series of the trigonometric functions Eq. (8), after tedious manipulation, the result turns out to be…”
Section: The Biharmonic Equation and The Biharmonic Solutionmentioning
confidence: 99%
“…In order to describe the experimental phenomenon [4,8] and make a good understanding on characteristics for magnetoelastic interaction of ferromagnetic bodies or structures, some theoretical models were proposed by different approaches, such as the Pao-Yeh model [2] from the axiomatic system, the Eringen-Maugin model [5,6] from the rational mechanical theorem, the magnetic couple model [4] and the magnetic force model [7] from the magnetic dipole model, and the variational principle model [9,31]. According to these models, the governing equation for magnetoelastic plate is as follows:…”
Section: Comparing With Other Theoretical Modelsmentioning
confidence: 99%